Association Between Matrix Metalloproteinase-9 C-1562T Gene Polymorphism and Ischemic Stroke - Ismail Kara; Tammam Sipahi; Aslı Sert Sunal; Mustafa Yıldız; Babürhan Güldiken (Türk Nöroloji Dergisi, 2023)
Objective: Matrix metalloproteinases (MMPs) are calcium-dependent zinc-containing proteases containing more than 28 enzymes that cause the degrading of the extracellular matrix. Although MMPs play key roles in many biological processes, they influence some pathological processes such as ischemic stroke (IS). Among MMPs, the enzyme most associated with IS is the MMP9 enzyme. This study aimed to evaluate the effect of the C-1562T (rs3918242) gene polymorphism of MMP9 on the development of IS in Turkish patients living in the Trakya Region. Materials and Methods: Our study involved 60 patients with IS and 60 controls. The patients with IS were categorized according to the Trial of ORG 10172 in Acute Stroke Treatment classification of stroke subtypes, and MMP9 C-1652T gene polymorphism was identified using polymerase chain reaction, followed by restriction fragment length polymorphism using the Pael (SphI) restriction enzyme. Results: Genotypes were defined as CC, CT, and TT according to the presence of C and T alleles. No significant differences were identified in the genotype distribution and allele frequency of MMP9 C-1562T gene polymorphism between the patients with IS and controls. Conclusion: Our findings suggest that MMP9 C-1562T gene polymorphism is not associated with the risk of IS in Turkish patients living in the Trakya Region.